Comparison of real-world treatment patterns in chronic lymphocytic leukemia management before and after availability of ibrutinib in the province of British Columbia, Canada. (April 2020) - Huang, Steven J.; Gerrie, Alina S.; Young, Sean; Tucker, Tracy; Bruyere, Helene; Hrynchak, Monica; Galbraith, Paul; Al Tourah, Abdulwahab J.; Dueck, Gregory; Noble, Michael C.; Ramadan, Khaled M.; Tsang, Peter; et al.
Highlights: Ibrutinib has replaced chemoimmunotherapy as preferred therapy in CLL during relapse. There has been an improvement in survival with introduction of ibrutinib. Allogeneic transplant is being used less in earlier lines with ibrutinib available. Abstract: We performed a retrospective study comparing treatment patterns and overall survival (OS) in chronic lymphocytic leukemia (CLL) patients with the advent of ibrutinib to provide current real-world data. Methods: Using a provincial population-based database, we analyzed CLL patients who received upfront treatment in British Columbia before ibrutinib availability (1984–2014), during ibrutinib access for: relapse only (2014–2015) and for upfront treatment of patients (with 17p deletion or unfit for chemotherapy) (2015–2016). Analysis included up to third-line treatment. Results: Of 1729 patients meeting inclusion criteria (median age, 66 years; 1466, period 1; 140, period 2; 123, period 3), FR was the most common first-line therapy (35.8 %, 54.3 % and 40.7 %, periods 1–3, respectively) and 18.7 % received ibrutinib upfront in period 3. The most common therapies in relapse were chemoimmunotherapy (36.1 % and 55.6 %, periods 1 and 2, second-line; 29.2 %, period 1, third-line) and ibrutinib (69.8 %, period 3, second-line; 46.4 % and 70.3 %, periods 2 and 3, third-line). OS improved for patients treated in periods 2–3 over period 1 (median OS not reached vs. 11.9 years, p < 0.001; no difference in OS for periods 2–3, p = 0.385). Conclusion: Ibrutinib has replaced chemoimmunotherapy as the preferred therapy in relapse. Overall survival has improved over time with access to ibrutinib.